Severity and pattern of injuries caused by the traditional Swiss team sport 'Hornussen': first retrospective study at a level I trauma centre in Switzerland. Issue 1 (18th August 2016) - Waterkamp, Volkmar; Ricklin, Meret; Schaller, Benoît; Katsoulis, Konstantinos; Exadaktylos, Aristomenis
Abstract : Background: This article addresses typical injury patterns related to the traditional Swiss team sport of Hornussen. A small plastic disk is struck with a special elastic racket and then intercepted in the field. Severe injuries have occasionally been reported. We present a systematic review of all cases of Hornussen injuries treated in the University Hospital of Bern from 2000 to 2014. Methods: To assess the frequency, type and outcome of Hornussen injuries, we performed a database search of all inpatient and outpatient cases related to Hornussen and that were admitted to and/or treated in Bern University Hospital from 2000 to 2014. Results: A total of 28 such patients could be identified. Apart from 1 woman injured as a bystander and treated as an outpatient, all patients were male and active players. Typical injury patterns comprised midfacial fractures and severe ocular traumata, very often in combination. Almost all of these patients had to be hospitalised due to the severity of the trauma suffered and underwent surgery. 1 patient had to be admitted to the intensive care unit prior to the operation. Conclusions: Eye and face injuries caused by Hornussen can be devastating. This resembles the potential risk of other bat-and-ball sports, such as cricket and baseball. Apart from the economic loss due to treatment costs and sick leave, these injuries can be disabling for life. It should therefore be mandatory for all players to wear protective gear, as is already the case for Hornussen players born in 1984 or later.